2008 kurak yılının Termessos (Güllük Dağı) Milli Parkı (Antalya) vejetasyonuna etkisinin çeşitli kuraklık indeksleriyle incelenmesi - Mehmet Ali Çelik; Murat Karabulut (Coğrafi Bilimler Dergisi, 2015)
Studies performed with regard to drought are based on conventional methods in general. The studies which are performed with conventional methods fill a significant gap. But, data belonging to climate are not sufficient alone for following a complex phenomenon such as drought, due to the fact that they are unable to pertain to long-time and are insufficient It is a great necessity that climate data should be enriched via satellite images in order to determine drought location and severity and that current drought conditions should be followed in a complete, update and detail way. In this study, we used satellite data with 16-days and monthly of temporal and 250-m and 1-km of spatial resolution, belonging to TERRA platform of MODIS satellite. From these data, various vegetation index models were created. We compared findings which were obtained using different methods with each other. Therefore, we not only confirmed information which were obtained about drought phenomenon, but also answered the question of which method reflected dry (arid) conditions better. Replied questions in our study also satellite-based vegetation index provided important conveniences in understanding and forecasting drought phenomenon